Pendampingan Guru PAUD Alamanda dalam Penerapan Play Based Learning untuk Pengenalan Warna pada Anak Usia Dini di Desa Padamaju - Eva Manfaatin; Imas Masitoh; Alfa Rohmatin; Lelis Nuramalia; Raihana Ahlush Shuffah; Ira Faoza; Sinta Trisnawati (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
Early childhood education is a fundamental stage in shaping children's cognitive, social, emotional, and motor development. However, learning practices in many early childhood institutions still rely on conventional methods that make children passive and less engaged. This community service program was implemented at PAUD Alamanda in Padamaju Village with a focus on introducing color concepts through play-based learning strategies. The objective of this program was to enhance the quality of science learning that is more interactive, enjoyable, and developmentally appropriate, while also strengthening teachers’ capacity in designing innovative learning strategies. The method applied was Participatory Action Research, conducted in several stages including observation and coordination, teacher training, implementation of play activities with children, and reflection and evaluation. The results revealed that children became more enthusiastic, successfully recognized primary and secondary colors, and demonstrated improvements in fine motor skills, creativity, and social interaction. Teachers also gained new insights into the application of more varied and innovative teaching methods. Overall, this program successfully bridged the gap between early childhood education theories emphasizing play-based learning and classroom practices, and contributed positively to the improvement of early childhood education quality.